A kinemtic and temporal analysis of ergometer rowing and on-water rowing - Upson, D. (Southern Connecticut State University, 2003)
In general the ergometer, the ergometer with slides and on-water rowing are similar. All three require the same basic movements, but there is enough difference that could affect rowing performance. Timing and technique are important components to effective rowing and practicing a similar technique is sufficient, but it is not necessarily efficient. If a rowing simulator is necessary for training during inclement weather, then the most accurate simulator is essential. During the statistical analysis, the ergometer with slides was not significantly different from both the ergometer and on-water rowing. The data for the ergometer with slides and on-water rowing led the researcher to conclude that the ergometer with slides emulated on-water rowing more accurately then the ergometer without slides. The ergometer with slides simulates the run of the boat, solicits similar body angles at the finish, and has the same timing of the stroke as the boat. The subjects reported that it was easier to maintain a higher stroke rate on the water and on the ergometer with slides. Subjects also stated that rowing on the ergometer with slides had the same feel as on-water rowing. Further research needs to be done to: determine the effects of the slides when they are linked together to form a four or eight man rowing machine for training purposes; how training on the ergometer with slides versus the ergometer effects on-water rowing performance; and how the ergometer with slides effects stroke rate and 500 meter splits. Quelle: http://www.southernct.edu/departments/graduatestudies/fellows/upson_diane.pdf